Diagnosis and antimicrobial therapy of infections caused by polyresistant microorganisms (updated 2024) - V. B. Beloborodov; O. V. Goloshchapov; V. G. Gusarov; A. V. Dekhnich; M. N. Zamyatin; K. N. Zolotukhin; N. A. Zubareva; S. K. Zyryanov; D. A. Kamyshova; N. N. Klimko; R. S. Kozlov; V. V. Kulabukhov; et al. (Вестник анестезиологии и реаниматологии, 2025)
Strains of microorganisms characterized by resistance to antimicrobial drugs used in medical organizations continue to spread in most regions of the world, including Russia. This naturally affects both the effectiveness of antimicrobial therapy and the tactics of its use not only in adults but also in children. The coronavirus pandemic has highlighted the growing problems with the treatment of invasive mycoses, the selection of dosage of antibacterial agents when using sorption and dialysis therapy methods. In combination with the registration of new antibacterial drugs ABSTRACT in Russia, this necessitated the need to make adjustments to the Methodological recommendations “Diagnostics and Antimicrobial Therapy of Infections Caused by Polyresistant Strains of Microorganisms” (2nd edition), prepared by a group of leading Russian experts in 2022 [1]. The presented version was approved in December 2024 at a joint meeting of representatives of public organizations: the Russian Association of Anesthesiologists-Intensivists, the Interregional public organization “Alliance of Clinical Chemotherapists and Microbiologists”, the Interregional Association for Clinical Microbiology and Antimicrobial Chemotherapy (IACMAC), the public organization “Russian Sepsis Forum”. These recommendations reflect the interdisciplinary consensus opinion on approaches to the diagnosis and antimicrobial therapy of infections caused by polyresistant microorganisms.